Optimization and Development of Ready to Eat Chocolate Coated Roasted Flaked Rice as Instant Breakfast Food - Kumar, Shiv (Foods, 2021)
The present study aimed to optimize and develop ready-to-eat rice-based functional breakfast food using response surface methodology. The levels of ingredients viz. skim milk powder, guar gum, and ferrous sulfate were pre-optimized and remained constant, whereas jaggery and dark chocolate were taken as independent variables. The optimum levels of jaggery and dark chocolate for chocolate-coated roasted flaked rice (CCRFR) were 8.49 g and 25.43 g, respectively. The physical, pasting, textural, functional, morphological, optical, and sensory characteristics of CCRFR and uncoated roasted flaked rice (RFR) were also studied. CCRFR had significantly higher mineral (iron and calcium) and total polyphenolic contents. Furthermore, the dimensional, sensory, and functional properties were also improved. The changes in morphological structure were also observed between the CCRFR and uncoated product using scanning electron microscopy. The coating adds nutritional value to the roasted rice and renders it an essential functional RTE convenience gluten-free cereal breakfast item.